Two Girls Named Blanche: Race, Gender, and Education in Halifax, 1880s–1920s - Fingard, Judith (Journal of the Royal Nova Scotia Historical Society, 2023)
This paper is a continuation of my research on the lives of late 19th century Black residents of Halifax. It focuses on two women—mother and daughter—who helped to undermine racial segregation in the city, first in secondary education and then in music education. Their personal determination helped to reduce the barriers for other Black women who followed them to high school and to the conservatory of music. I am grateful to Professor Michelle Williams, Dalhousie University Law Faculty, for the illustrations and some hitherto unknown documents.